Zinc Finger Proteins in Neuro-Related Diseases Progression - Bu, Siyuan; Lv, Yihan; Liu, Yusheng; Qiao, Sen; Wang, Hongmei (Frontiers in Neuroscience, 2021)
Zinc finger proteins (ZNF) are among the most abundant proteins in eukaryotic genomes. It contains several zinc finger domains that can selectively bind to certain DNA or RNA and associate with proteins, therefore, zinc finger proteins can regulate gene expression at the transcriptional and translational levels. In terms of neurological diseases, numerous studies have shown that many zinc finger proteins are associated with neurological diseases. The purpose of this review is to summarize the types and roles of zinc finger proteins in neuropsychiatric disorders. We will describe the structure and classification of zinc finger proteins, then focus on the pathophysiological role of zinc finger proteins in neuro-related diseases and summarize the mechanism of action of zinc finger proteins in neuro-related diseases.